The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1037/0003-066x.39.10.1113
|View full text |Cite
|
Sign up to set email alerts
|

Three Mile Island: Psychology and environmental policy at a crossroads.

Abstract: Summarizes the research on the psychological stress that was precipitated by the Three Mile Island (TMI) nuclear reactor accident and that could be caused by a restart of TMI's undamaged reactor. The legal background of whether the reactor should be turned on again is explained within the context of case law concerning recovery of damages caused by emotional trauma. Recent court decisions are explored for implications regarding the role of psychology in environmental use assessments that may be required by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…A growing literature poses that delayed or long-term effects can be significant (Figley, 1978; Davidson and Baum, 1986), and symptom resolution may be related inversely to elapsed time (Green et al, 1985). It is known that symptoms arise sharply after trauma, but in a review of studies of the Three Mile Island accident, Hartsough and Savitsky (1984) noted that most could not demonstrate longterm effects. Green et al, (1985) cited the important need for empirical evidence to determine whether there is a critical point beyond which symptom resolution is unlikely.…”
Section: Introduction Sloanmentioning
confidence: 97%
“…A growing literature poses that delayed or long-term effects can be significant (Figley, 1978; Davidson and Baum, 1986), and symptom resolution may be related inversely to elapsed time (Green et al, 1985). It is known that symptoms arise sharply after trauma, but in a review of studies of the Three Mile Island accident, Hartsough and Savitsky (1984) noted that most could not demonstrate longterm effects. Green et al, (1985) cited the important need for empirical evidence to determine whether there is a critical point beyond which symptom resolution is unlikely.…”
Section: Introduction Sloanmentioning
confidence: 97%
“…I could as readily have dealt with issues such as the impact of technology on the environment and the role that psychologists and other social scientists could play (Hartsough & Savitsky, 1984), or I could have paid attention to issues of workforce provision (Mauer, 1978) and labour relations (Eisinger & Levine, 1968;Bennett, 1969Bennett, -1971. On the other hand, as socially relevant issues I may have addressed problems surrounding the delivery of psychological services in the education system, and particularly in the rural areas (Helge, 19851, the role of psychology in multicultural education (Buckalew & Hickey, 1982), or even the possible involvement of psychologists in socialization in traditional societies (KagitGibasi, 1984), or in society in general (Smith, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…In reflecting on this issue, Tizard (1984) examined research concerning the 16 years of violence and conflict in Northern Ireland as well as the peak periods of anxiety over nuclear weapons in the United Kingdom and found little evidence for a precipitous rise in mental health-related problems that could be linked to these environmental events. Moreover, although stress levels among residents near Three Mile Island increased sharply as a result of the nuclear reactor accident in 1979, most studies demonstrated a decline in effects over time, and those investigations that did show long-term effects were unable to document their behavioral or clinical significance (see Hartsough & Savitsky, 1984). Tizard (1984) attributed the lack of long-term impact of these incidents to the resiliency and adaptability of young people in dealing with threats coming from outside their immediate environment.…”
Section: Discussionmentioning
confidence: 99%